NIMG-76. DISCRETE LOWER-GRADE GLIOMA (DLGG) VERSUS INFILTRATIVE LOWER-GRADE GLIOMA (ILGG): CORRELATION OF RADIOLOGICAL CHARACTERISTICS WITH CLINICAL OUTCOMES. (12th November 2021) - Ali Khan, Ahsan; Hamza Bajwa, Mohammad; Khan, Noman; Khalid, Muhammad Usman; Mubarak, Fatima; Ather Enam, Syed
Abstract: INTRODUCTION: Lower grade gliomas encompass grade 2 and 3 tumors. However, this term is more generalized and does not include the spectrum of radiological and tumor morphological patterns seen. Here we have established two distinct patterns of radiographic appearance seen within lower grade gliomas: ILGG and DLGG. Imaging plays a vital role in diagnosis, surveillance, characterization, and monitoring of intracranial tumors. Of particular importance is the differentiation of tumor features to reliably predict malignancy, tumor grade, possible molecular or genetic features, disease progression and recurrence, potential for malignant transformation, and postoperative outcomes. Our study will look at these radiographic characteristics of diffuse and infiltrating lower grade gliomas and discuss their predictive value. Understanding the distinct nature of these varieties of LGG will help us in surgical decision-making, prognostication, biopsy target and precision medicine. METHODS: Pre-operative and post-operative MRI images of Grade 2 and 3 tumors were identified and analyzed in order to extract radiographic data, and correlated with patient demographics, clinical outcomes, extent of surgical resection, and molecular genetic analysis. RESULTS: Out of 35 patients evaluated, 22 (62.9%) were labeled ILGGs and 13 (37.1%) were deemed DLGGs according to the pre-defined criteria. T2 habitat was higher in ILGG (mean = 2162) than DLGG (mean = 1482) as well as size, in cm (6.02 vs. 4.92). ADC habitat, lesion ADC, and percentage of the lesion that showed contrast-enhancement were similar. T2-FLAIR mismatch was significantly higher in ILGG (p = 0.02). Post-operative KPS scores were significantly higher in the DLGG group (p = 0.03). CONCLUSION: T2-FLAIR mismatch can be a significant classifier for lower-grade gliomas. Our study shows there are differences in tumor morphology of diffuse and infiltrative lower-grade gliomas which can be correlated to outcomes after surgery. *Indicates corresponding author.